2014
DOI: 10.1371/journal.pone.0090664
|View full text |Cite
|
Sign up to set email alerts
|

The Road to Tuberculosis (Mycobacterium tuberculosis) Elimination in Arkansas; a Re-Examination of Risk Groups

Abstract: ObjectivesThis study was conducted to generate knowledge useful for developing public health interventions for more effective tuberculosis control in Arkansas.MethodsThe study population included 429 culture-confirmed reported cases (January 1, 2004–December 31, 2010). Mycobacterium tuberculosis genotyping data were used to identify cases likely due to recent transmission (clustered) versus reactivation (non-clustered). Poisson regression models estimated average decline rate in incidence over time and assesse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
27
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 12 publications
(30 citation statements)
references
References 18 publications
3
27
0
Order By: Relevance
“…Figures 4A and 4B compare model outputs with results from a recent molecular epidemiology study in which the large majority (87%) of culture-confirmed isolates from TB cases in Arkansas during the period 2004–2010 were genotyped (spoligotype and 12-locus MIRU-VNTR) to identify transmission clusters [21]. In that study, a cluster is defined as at least two cases diagnosed within a year from each other, caused by Mycobacterium tuberculosis isolates sharing the same molecular typing, independently of known epidemiological links [21].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Figures 4A and 4B compare model outputs with results from a recent molecular epidemiology study in which the large majority (87%) of culture-confirmed isolates from TB cases in Arkansas during the period 2004–2010 were genotyped (spoligotype and 12-locus MIRU-VNTR) to identify transmission clusters [21]. In that study, a cluster is defined as at least two cases diagnosed within a year from each other, caused by Mycobacterium tuberculosis isolates sharing the same molecular typing, independently of known epidemiological links [21].…”
Section: Resultsmentioning
confidence: 99%
“…In that study, a cluster is defined as at least two cases diagnosed within a year from each other, caused by Mycobacterium tuberculosis isolates sharing the same molecular typing, independently of known epidemiological links [21]. The Arkansas molecular epidemiological study found that 61% of cases were non-clustered, a figure well below the national average of 77% [27] because of the time-restricted cluster definition [21]. The fraction of clustered cases is often considered as a proxy of recently transmitted cases (e.g.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…TB disease attributable to RT represents active transmission in a population, which can be interrupted by prompt public health intervention (2). Measuring TB attributable to RT provides a tool with which public health programs can focus limited public health resources and track progress in TB control efforts to interrupt transmission (36). …”
mentioning
confidence: 99%